A CaSSIS and HiRISE map of the Clay-bearing Unit at the ExoMars 2022 landing site in Oxia Planum. (May 2022) - Bowen, Adam Parkes; Bridges, John; Tornabene, Livio; Mandon, Lucia; Quantin-Nataf, Cathy; Patel, Manish R.; Thomas, Nicolas; Cremonese, Gabriele; Munaretto, Giovanni; Pommerol, Antoine; Pajola, Maurizio
Abstract: In preparation for the operations of the ExoMars Rosalind Franklin rover, characterising its landing site in Oxia Planum is essential. Of particular interest is the extensive Clay-bearing Unit present at the site, a key target in the search for biosignatures. In this paper we provide a map based on variations in colour and spectral information within this unit, covering the 1σ landing envelope of the rover along with a 1 ​km buffer to account for minor shifts of the landing envelope ahead of launch (referred to going forward as the 1σ+ landing envelope). We used imagery from the Colour and Stereo Surface Imaging System (CaSSIS) and High Resolution Imaging Science Experiment (HiRISE) instruments, along with CaSSIS Band Ratio Composites with enhanced colour sensitivity to the presence of ferric (Fe 3+ ) and ferrous (Fe 2+ ) iron bearing materials. Our map is of a far higher resolution (map-scale 1:2000) than those previously available and, in contrast to previously available maps of this unit, differentiates between an Orange Subunit and a Blue Subunit which make up the Clay-bearing Unit. This mapping covered the ∼91% of the 1σ+ landing envelope where there was CaSSIS coverage and split the Clay-bearing Unit into three categories: one for each of the clay subunits, and another for exposures of the Clay-bearing Unit where either both subunits were too intermixed to reliably separate, or where it was difficult to determine which of the two were present. The results from our mapping shows that at least ∼35% of the 1σ+ envelope is covered by exposures of the Clay-bearing Unit: ∼18% by the Orange Subunit, ∼9% the Blue Subunit, and ∼12% were classified as Indeterminate. The spread of these two subunits varied substantially over the 1σ+ landing envelope, with the south-east half of the landing envelope dominated by the Orange Subunit (∼70% exposures in this area belonging to the Orange Subunit, ∼10% to the Blue Subunit and ∼20% to the Indeterminate category), while the north-west has more sporadic exposures of the Clay-bearing Unit (∼22% Orange, ∼37% Blue and ∼41% Indeterminate). The colour distinction between the two subunits is thought to be due to constituent mineralogical differences rather than differences in dust coverage of the two subunits. The scale of the fracturing present in the two subunits has also been assessed in this study, via qualitative observations of the fracture length and quantitative mapping out of fracture networks. While there were differences in the scale of fracturing between the two subunits, these were not as great as had previously been identified. Graphical abstract: Image 1 Highlights: CaSSIS and HiRISE used to map clay unit at Oxia Planum, landing site of ExoMars. This map distinguishes between two subunits which make up the clay-bearing unit. Band ratio CaSSIS imagery aided distinguishing subunits by their Fe3+/Fe2+ content. Potential causes of clay-bearing unit variation were assessed. Fracturing present within two subunits was generally found to be indistinguishable.